The relevant practices of ERG theory of motivation toward job satisfaction / Nurfaiza Ibrahim - Ibrahim, Nurfaiza (2004)
Job satisfaction is very important while perform the job in the organization. Some people did not know how important job satisfaction when perform the job. This research tries to introduce ERG Theory of Motivation to achieve job satisfaction. ERG Theory of Motivation was introduce by the Clayton Alderfer. This theory include the Existence Needs (Physiological, safety and security), Relatedness Needs (Social and Self- Esteem) and Growth (self- actualization). From the Literature review, all this need will influence the level of job satisfaction. The researcher was select Kastam Di Raja Ayer Keroh as the location of the study. 50 Respondents was select randomly to answer the question. To analyze the data, SPSS had been used. Finding and analysis shows that there are many not significant associations between job satisfaction and independent variable. But if we look at the ranking of the independent variable, we see that shelter can give positive association to the job satisfaction. The researcher also provides several recommendations at the last of this chapter. The manger of the organization can used this recommendation to increase the level of satisfaction, Finally, the researcher found that ERG Theory is not really relevant to practice at public organization.